THE IMPORTANCE OF WATER-SAVING TECHNOLOGIES AT A TIME WHEN WATER SCARCITY IS GROWING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Today, efforts are being made to understand water and its problems, the growing demand for water and the underlying causes of water resource depletion. The main issue is the rational and efficient use of water, aimed at improving the reclamation of irrigated lands. Basically, the reforms carried out in our country in the last 5-6 years have shown their positive effect in the water sector, the use of water-saving technologies, and the tasks being solved in this regard will expand the scope of application of water-saving technologies. will be introduced in the future, will allow for a significant increase. Uzbekistan is also implementing important measures related to the rational use of water resources.